The Association Between Body Mass Index and the Risk of Hospitalization and Mortality due to Infection: A Prospective Cohort Study. (11th October 2020) - Yang, Wei-Shun; Chang, Yi-Cheng; Chang, Chia-Hsuin; Wu, Li-Chiu; Wang, Jiun-Ling; Lin, Hsien-Ho
Abstract: Background: We aim to determine whether obesity increases the risk of various infections using a large prospective population-based cohort. Methods: A total of 120 864 adults were recruited from the New Taipei City health screening program from 2005 to 2008. Statistics for hospitalization and mortality due to infection were obtained from the National Health Insurance Database and the National Death Registry in Taiwan. Results: During a mean follow-up period of 7.61 years, there were 438, 7582, 5298, and 1480 first hospitalizations due to infection in the underweight, normal, overweight, and obese groups, respectively. Obesity significantly increases the risk of hospitalization for intra-abdominal infections (adjusted hazard ratio [aHR], 1.19; 95% CI, 1.00–1.40), including diverticulitis, liver abscess, acute cholecystitis and anal and rectal abscess, reproductive and urinary tract infection (aHR, 1.38; 95% CI, 1.26–1.50), skin and soft tissue infection (aHR, 2.46; 95% CI, 2.15–2.81), osteomyelitis (aHR, 1.70; 95% CI, 1.14–2.54), and necrotizing fasciitis (aHR, 3.54; 95% CI, 1.87–6.67), and this relationship is dose-dependent. This study shows that there is a U-shaped association between body mass index (BMI) and hospitalization for lower respiratory tract infection, septicemia, and the summation of all infections and that underweight people are at the greatest risk, followed by obese people. There is a clear negative relationship between BMI and infection-related mortality. Conclusions: The pattern that BMI affects the risk of hospitalization and mortality due to infection varies widely across infection sites. It is necessary to tailor preventive and therapeutic measures against different infections in hosts with different BMIs.